The Impact of Green Skepticism on the Effectiveness of Green Promotion in Driving Green Purchase Behavior in Indonesia - Nediva Trisha Kanya Wijaya; Amalia E. Maulana (Publikasi Indonesia, 2025)
Growing consumer concern about environmental impact has prompted companies to adopt green marketing strategies. However, the rise of green skepticism, often triggered by greenwashing, raises questions about the actual effectiveness of such strategies. This study examines the impact of eco-labels and green advertising on green purchase behavior, with perceived green knowledge as a mediator and green skepticism as a moderator. Drawing from the Persuasion Knowledge Model (PKM) and the Stimulus–Organism–Response (S–O–R) framework, a quantitative survey was conducted with 301 environmentally conscious consumers in Greater Jakarta. Structural equation modeling (PLS-SEM) was used to test the hypotheses. Results show that both eco-labels and green advertising significantly enhance perceived green knowledge, which positively influences green purchase behavior. Interestingly, green skepticism negatively moderates the effect of green advertising on perceived knowledge, but does not weaken the influence of eco-labels—possibly due to their third-party verification. The findings emphasize the importance of credible and transparent green communication. Theoretically, this study extends S–O–R by validating direct stimulus-response pathways. Practically, it guides marketers and policymakers to prioritize substantiated claims over persuasive imagery in green promotions.